Digital Learning: A Solution for More Inclusive and Affordable Education - Syofianis Ismail; Zhang Ling (International Journal of Education and Digital Learning (IJEDL), 2025)
Digital learning has emerged as a transformative tool in education, offering a pathway to more inclusive and affordable learning opportunities for all students, regardless of their geographical location, socio-economic status, or background. This article explores how digital learning can address persistent challenges in traditional educational systems, such as limited access to quality education, high costs, and unequal distribution of resources. By leveraging technologies like e-learning platforms, mobile apps, and virtual classrooms, digital learning has the potential to bridge the education gap and provide flexible learning opportunities tailored to individual needs. The study reviews the benefits of digital learning, including increased accessibility, personalized learning experiences, and the democratization of education. However, the article also discusses the challenges of digital learning, such as the digital divide, lack of technological infrastructure, and the need for teacher training. Drawing on existing research and case studies, this paper examines the role of digital learning in promoting educational equity and affordability. It concludes by highlighting the importance of policy intervention and investment in technology to ensure that digital learning becomes a sustainable and effective solution for education in the 21st century.